Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

The impact of school activity space layout on children's physical activity levels during recess: An agent -based model computational approach - Jiameng Cui; Xue Meng; Siming Qi; Junwen Fan; Wenxuan Yu; Hongxing Liu; Xiang Wang; Yu Zhang (Building and Environment, 2025)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Corrigendum to “Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage” [Food Chem. Toxicol. 178 (2023) 113915] - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

Dibutyl phthalate induces liver fibrosis via p38MAPK/NF-κB/NLRP3-mediated pyroptosis - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Dibutyl phthalate causes heart damage by disrupting Ca2+ transfer from endoplasmic reticulum to mitochondria and triggering subsequent pyroptosis - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Power performance of an asymmetric wave energy converter near a partial reflection wall - Binzhen Zhou; Qi Zhang; Jianjian Hu; Peng Jin; Hengming Zhang; Siming Zheng (Ocean Engineering, 2023)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)